Cluster Headache and Its Cousins: A Family of Pain Management Problems - John Edmeads (Pain Research and Management)
Cluster headache causes great misery because of the severity, frequency and repetitiveness of its attacks, and the fear (justified in a few sufferers) that the attacks will respond to nothing and will never cease. For most people with cluster headaches there is effective treatment, both for the acute attacks (subcutaneous sumatriptan, injected dihydroergotamine and oxygen inhalation) and for prophylaxis (verapamil, valproate, ergotamine, methysergide, lithium carbonate and corticosteroids). For the 10% of suffers who respond to no medications, or have to discontinue them because of serious adverse effects, surgical ablation of the trigeminal root or nervus intermedius is a last resort that helps only some. Correct diagnosis is an essential prelude to an appropriate treatment. Serious disease such as carotid dissection, and aneurysm may occasionally mimic cluster headache, but seldom perfectly enough to confuse a careful clinician. In terms of sorting out the diagnosis, the recently recognized relatives of cluster headache -- chronic and episodic paroxysmal hemicrania, and short-lasting unilateral neuralgiform headache with conjunctival injection and tearing syndrome -- are more problematic. These are important to recognize because they do not respond to 'cluster treatment', but the paroxysmal hemicranias respond to indomethacin, whereas the cluster headache does not. A more distant family member, hemicrania continua, is usually, but not always, responsive to indomethacin and sometimes bears a passing resemblance to cluster headache. An unrelated entity, hypnic headache, has confused a few clinicians who did not bear in mind that a detailed history is the key to headache diagnosis.